Effect of marine heatwaves on the immune response of white seabream Diplodus sargus supplemented with macroalgae - Tavares, Sara Sofia Rosado (2024)
Tese de mestrado, Ecologia Marinha, 2024, Universidade de Lisboa, Faculdade de Ciências